Analytical and experimental investigation of flexible longitudinal zigzag structures for enhanced multi-directional energy harvesting. (7th February 2017) - Zhou, Shengxi; Hobeck, Jared D; Cao, Junyi; Inman, Daniel J
Abstract: This paper makes a complete investigation of flexible longitudinal zigzag (FLZ) energy harvesters for the purpose of enhancing energy harvesting from low-frequency and low-amplitude excitation. A general theoretical model of the FLZ energy harvesters with large joint block mass is proposed. In order to verify the accuracy of the theoretical model, both experimental results and finite element analysis via ANSYS software are presented. Results show that the theoretical model can successfully predict the dynamic response and the output power of the FLZ energy harvesters. Both theoretical and experimental results demonstrate that the proposed energy harvesters can effectively harvest vibration energy even when the direction of excitation relative to the harvester varies from 0° to 90°. Under the low excitation level of 0.18 m s −2, the experimental maximum output power of a FLZ energy harvester with five beams was found to be 1.016 mW. Finally, the results indicate that the proposed structure is capable of effective energy conversion across a large range of excitation angles at low-frequency and low-amplitude excitations, which makes it suitable for a wide range of working conditions.